2018
DOI: 10.1029/2018jb016048
|View full text |Cite
|
Sign up to set email alerts
|

P Wave Anisotropic Tomography of the SE Tibetan Plateau: Evidence for the Crustal and Upper‐Mantle Deformations

Abstract: The upper crust in the SE Tibetan Plateau is rotating around the eastern Himalayan syntax clockwise, and the western margin of the Yangtze Craton has been involved in the active tectonics. However, it is still unclear whether and how the deep crust and upper mantle respond to the plateau expansion. In this study we present a high‐resolution three‐dimensional model of P wave velocity tomography and azimuthal anisotropy in the crust and uppermost mantle beneath the SE Tibetan Plateau determined using traveltime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 90 publications
(209 reference statements)
1
46
0
Order By: Relevance
“…The picking accuracy is ~0.1 s for P wave arrivals and ~0.25 s for S wave arrivals. The data set has been used to determine a 3‐D P wave velocity model of the crust and upper mantle beneath the SE Tibetan Plateau by Huang et al (). All the local events have been well relocated with the obtained 3‐D velocity model (see Huang et al, , for details).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The picking accuracy is ~0.1 s for P wave arrivals and ~0.25 s for S wave arrivals. The data set has been used to determine a 3‐D P wave velocity model of the crust and upper mantle beneath the SE Tibetan Plateau by Huang et al (). All the local events have been well relocated with the obtained 3‐D velocity model (see Huang et al, , for details).…”
Section: Methodsmentioning
confidence: 99%
“…We inverted the local earthquake arrival times and teleseismic relative travel‐time residuals simultaneously for 3‐D P and S wave velocity (Vp, Vs) models of the crust and upper mantle beneath the SE Tibetan Plateau using the method of Zhao et al (, ). The starting 1‐D velocity model is modified from the AK135 velocity model (Kennett et al, ) according to the local travel‐time curves (see Huang et al, , for details; Figure S2). The Moho topography is derived from the surface wave and receiver function analyses (Pasyanos et al, ; Wang et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…Specifically, the model of lower crustal flow explains the crustal thickening in the Tibetan margin well and has been supported by geophysical results in recent years, including high‐conductivity anomalies (e.g., Bai et al, 2010), low‐velocity anomalies (e.g., Bao et al, 2015; M. Chen et al, 2014; Fu et al, 2017; Z. Huang et al, 2018; Liu et al, 2014; W. Wang et al, 2014; Wei et al, 2013; Yao et al, 2008, 2010), and positive radial anisotropies ( V SH > V SV ) (H. Huang et al, 2010; Xie et al, 2017) and by GPS measurements (Shen et al, 2005). Previous receiver function studies have shown a gentle variation in the Moho topography from the Tibetan Plateau to the Yangtze Craton (e.g., Sun et al, 2012; W. Wang et al, 2017; X. Xu et al, 2013), consistent with the Moho variation predicted by the lower crustal flow model.…”
Section: Introductionmentioning
confidence: 64%
“…We consider only a 4% anisotropy single-layer crust with a horizontal axis of symmetry in the S wave velocity. This anisotropy is considerably stronger than the average (Crampin, 1994;Z. Huang et al, 2018;Ji et al, 2015;Ji & Salisbury, 1993;Tatham et al, 2008;.…”
Section: Influence Of a Tilted Mohomentioning
confidence: 84%
“…According to the recent revealed smoothed Moho topography (Z. Huang et al, 2018;Pasyanos et al, 2014;W. Wang et al, 2017), the Moho raises to the depth of~52 km approximately 70 km to the northwest (i.e., at 30.3°N to 99.5°E) and drops to a depth of~65 km approximately 70 km to the southeast (i.e., at 29.5°N to 101°E).…”
Section: Journal Of Geophysical Research: Solid Earthmentioning
confidence: 99%